Pergantian Auditor, Opini Audit, Financial Distress dan Audit Delay - Indrayani, Putu; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 31 No 4 (2021)DO - 10.24843/EJA.2021.v31.i04.p07, 2021)
Audit Delay is a period of time to complete the audit task from the closing date of the financial year to the date of completion of the audit report by an independent auditor. The purpose of this research is to examine whether there is an influence between auditor turnover, audit opinion and financial distress towards audit delay or not. This research was conducted at mining companies on the Bursa Efek Indonesia (BEI). There number of samples taken was 144, with nonprobability sampling method, especially purposive sampling. Data collection was carried out by non-participant observation. The analysis technique used is multiple linear regression analysis. The results of the analysis found that auditor switching had no effect on audit delay. These indicates prove that wether there is a change of auditors or not has doesn’t affect the audit delay. Opinion of audit brought a negative effect on audit delay. Financial distress brought a positive effect on audit delay. Keywords: Audit Delay; Auditor Switching; Auditor Opinion; Financial Distress.